Eficiência: Sua diversidade e seus paradoxos - Valdir Melo (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– The word "efficiency" has several technical meanings. Some of them are confused with productivity, with economies of scale and with optimization. There are also some lay meanings which are vague enough; they allude to effectiveness, to competence, to adequacy, to doing something well, and to quickness, among others. For these and for other reasons, part of the economic literature asserts that the importance of efficiency has been exaggerated. Appraisals of the efficiency of a productive activity may be disparate or incongruent when the activity has more than one aim. Moreover, seeking efficiency may fail to match with seeking security as well as with inventing and innovating.
Keywords: D73; A13; B40; 330; efficiency; effectiveness; productivity; economies of scale; optimization